What are we - Abdullah, Aimy (Universiti Teknologi MARA, Kedah, 2025)
This anthology of patriotic poetry stands as a testament to the enduring spirit of Merdeka and the creative talents of our esteemed academics from the UTM system. As we celebrate the anniversary of Malaysia's independence, this collection offers a unique glimpse into the hearts and minds of our scholars. Through their evocative words, these academics have woven a rich tapestry of emotions, experiences, and reflections on our nation's journey. Their poems explore the profound themes of freedom, unity, and national pride, offering a fresh perspective on what it means to be Malaysian. We are grateful for the contributions of all the participating academics, whose dedication and passion have made this anthology possible. Their willingness to share their thoughts and creativity has enriched our understanding of Merdeka and inspired us to cherish our nation's heritage. This anthology is more than just a collection of poems; it is a celebration of our nation's past, present, and future. Let us continue to uphold the spirit of Merdeka, strive for excellence, and build a Malaysia that we can all be proud of.